Capacity of Health Facilities to Manage Hypertension in Mukono and Buikwe Districts in Uganda: Challenges and Recommendations - Musinguzi, Geofrey; Bastiaens, Hilde; Wanyenze, Rhoda K.; Mukose, Aggrey; Geertruyden, Jean- Pierre Van; Nuwaha, Fred (PLoS ONE, 2015)
The burden of chronic diseases is increasing in both low- and middle-income countries. However, healthcare systems in low-income countries are inadequately equipped to deal with the growing disease burden, which requires chronic care for patients. The aim of this study was to assess the capacity of health facilities to manage hypertension in two districts in Uganda. Methods In a cross-sectional study conducted between June and October 2012, we surveyed 126 health facilities (6 hospitals, 4 Health Center IV (HCIV), 23 Health Center III (HCIII), 41 Health Center II (HCII) and 52 private clinics/dispensaries) in Mukono and Buikwe districts in Uganda. We assessed records, conducted structured interviews with heads of facilities, and administered questionnaires to 271 health workers. The study assessed service provision for hypertension, availability of supplies such as medicines, guidelines and equipment, in-service training for hypertension, knowledge of hypertension management, challenges and recommendations. Results Of the 126 health facilities, 92.9% reported managing (diagnosing/treating) patients with hypertension, and most (80.2%) were run by non-medical doctors or non-physician health workers (NPHW). Less than half (46%) of the facilities had guidelines for managing hypertension. A 10th of the facilities lacked functioning blood pressure devices and 28%
Keywords: Health Facilities; Mukono; Buikwe; Districts; Uganda